Effects of Dietary Chlorogenic Acid Supplementation Derived from Lonicera macranthoides Hand-Mazz on Growth Performance, Free Amino Acid Profile, and Muscle Protein Synthesis in a Finishing Pig Model. (12th March 2022) - Wang, Wenlong; Li, Fengna; Duan, Yehui; Guo, Qiuping; Zhang, Lingyu; Yang, Yuhuan; Yin, Yunju; Han, Mengmeng; Gong, Saiming; Li, Jianzhong; He, Shanping; Yin, Yulong
Abstract : Chlorogenic acid (CGA), as one of the richest polyphenol compounds in nature, has broad applications in many fields due to its various biological properties. However, initial data on the effects of dietary CGA on protein synthesis and related basal metabolic activity has rarely been reported. The current study is aimed at (1) determining whether dietary CGA supplementation improves the growth performance and carcass traits, (2) assessing whether dietary CGA alters the free amino acid profile, and (3) verifying whether dietary CGA promotes muscle protein synthesis in finishing pigs. Thirty-two (Large × White × Landrace) finishing barrows with an average initial body weight of 71.89 ± 0.92 kg were randomly allotted to 4 groups and fed diets supplemented with 0, 0.02%, 0.04%, and 0.08% CGA, respectively. The results indicated that, compared with the control group, dietary supplementation with 0.04% CGA slightly stimulated the growth performance of pigs, whereas no significant correlation was noted between the dietary CGA levels and animal growth (P > 0.05 ). Furthermore, the carcass traits of pigs were improved by 0.04% dietary CGA (P < 0.01 ). In addition, dietary CGA significantly improved the serum free amino acid profiles of pigs (P < 0.01 ), while 0.04% dietary CGA promoted more amino acids to translocate to skeletal muscles (P < 0.05 ). The relative mRNA expression levels of SNAT2 in both longissimus dorsi (LD) and biceps femoris (BF) muscles were augmented in the 0.02% and 0.04% groups (P < 0.05 ), and the LAT1 mRNA expression in the BF muscle was elevated in the 0.02% group (P < 0.05 ). We also found that dietary CGA supplementation at the levels of 0.04% or 0.08% promoted the expression of p-Akt and activated the mTOR-S6K1-4EBP1 axis in the LD muscle (P < 0.05 ). Besides, the MAFbx mRNA abundance in the 0.02% and 0.04% groups was significantly lower (P < 0.05 ). Our results revealed that dietary supplementation with CGA of 0.04% improved the free amino acid profile and enhanced muscle protein biosynthesis in the LD muscle in finishing pigs.